The proof provided has a "fundamental error" in it, but I can't figure out what the error is.
Statement: For all non-negative integers n, n is even.
Proof: Let P(n) be the open sentence: n is even.
Base Case: We show that P(0) is true. Since 0=2(0), then 0 is even and the statement is true for n=0
Inductive Hypothesis: We assume the P(i) is true for 0≤i≤k. That is, i is even for all i in the range 0≤i≤k for some k∈Z for k≥0.
Inductive Conclusion: We show that P(k+1) is true. Conside k+1. Since k+1=k−1+2 and since 0≤k−1≤k, the by the inductive hypothesis, k−1 is even and 2 is even. The sum of two even numbers is even, and thus k+1 is even as required.
Obviously this is not true, and I have an idea as to the error, but I'm not 100% sure. I think it has something to do with the fact that they are using the strong induction method in the hypothesis, but have only provided 1 base case. Other than that, I can't see anything wrong with the actual proof method (but the proof is obviously wrong).
Answer
Let us rewrite the inductive step instantiated for k=0:
Inductive Conclusion: We show that P(1) is true. Conside 1. Since 1=−1+2 and since 0≤−1≤0, the by the inductive hypothesis, −1 is even and 2 is even. The sum of two even numbers is even, and thus 1 is even as required.
No comments:
Post a Comment